2009
DOI: 10.2478/s11534-009-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Collisions between discrete spatiotemporal dissipative Ginzburg-Landau solitons in two-dimensional photonic lattices

Abstract: Abstract:Systematic results of collisions between discrete spatiotemporal dissipative Ginzburg-Landau solitons in two-dimensional photonic lattices are reported. The generic outcomes are identified for (i) the collision of two identical solitons located in the corner, at the edge, and in the center of the photonic lattice, and for (ii) the collision of two non-identical corner and edge solitons located at different distances from the boundaries of the photonic lattice. Depending on the values of the kick (coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Since their theoretical prediction in 1973 and experimental demonstration in 1980 [1,2], optical solitons have been the subject of intense theoretical and experimental studies in nonlinear optics [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In particular, optical spatial solitons, which exhibit the fascinating characteristics of self-guided beams, are an attractive and active area of research, because of their potential applications in many areas, including all-optical switching, optical data storage, distribution, and processing [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Since their theoretical prediction in 1973 and experimental demonstration in 1980 [1,2], optical solitons have been the subject of intense theoretical and experimental studies in nonlinear optics [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In particular, optical spatial solitons, which exhibit the fascinating characteristics of self-guided beams, are an attractive and active area of research, because of their potential applications in many areas, including all-optical switching, optical data storage, distribution, and processing [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Then, in region ℎ, a different type of collision reported in Ref. [26] appears instead. In this case, both the solitons dissipate with in-phase collision as shown in Fig.…”
mentioning
confidence: 72%
“…Depending on the collisional momentum 𝑃 and gain/loss coef-ficients, four generic dynamics are identified: at small 𝑃 , there appears to be merger of the solitons into a single whose velocity can be modulated by 𝜙; at large 𝑃 , quasi-elastic interactions arise; in the intermediate region with high gain (low loss), an extra soliton will be created whose velocity linearly varies with 𝜙; otherwise, with low gain (high loss), the two solitons dissipate at in-phase, whereas one of them keeps original velocity with 𝜙 ̸ = 0. [26] We consider the CQ CGL equation in a general form of [11,12]…”
mentioning
confidence: 99%
“…The study of optical solitons has attracted a lot of interest and many results have been reported during the past couple of decades [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A substantial amount of research results on Thirring solitons has been reported in the past [1,[3][4][5][24][25][26].…”
Section: Introductionmentioning
confidence: 99%